Impedance Spectroscopic Study of p-i-n Type a-Si Solar Cell by Doping Variation of p-Type Layer. (29th April 2012) - Lee, Sunhwa; Park, Seungman; Park, Jinjoo; Kim, Youngkuk; Park, Hyeongsik; Jang, Juyeun; Shin, Chonghoon; Lee, Youn-Jung; Baek, Seungsin; Kim, Minbum; Jung, Junhee; Yi, Junsin
Abstract : We investigated p-i-n type amorphous silicon (a-Si) solar cell where the diborane flow rate of the p-type layer was varied and the solar cell was measured static/dynamic characteristics. The p/i interface of the thin film amorphous silicon solar cells was studied in terms of the coordination number of boron atoms in the p layer. p-type layer and p/i interface properties were obtained from the X-ray photoelectron spectroscopy (XPS) and impedance spectroscopy. One of the solar cells shows open circuit voltage ( V oc ) = 880  mV, short circuit current density ( J sc ) = 14.21  mA/cm 2, fill factor ( FF ) = 72.03 %, and efficiency ( η ) = 8.8 % while the p-type layer was doped with 0.1%. The impedance spectroscopic measurement showed that the diode ideality factor and built-in potential changed with change in diborane flow rate.